Students’ Pursuit of Knowledge in Islam: Framework for Character Education from Quran and Hadith - Nuha Sufina Binti Saidi; Mutathahirin Mutathahirin; Nur Akashah Binti Zulkefli; Dasrizal Dasrizal (Muaddib: Journal of Islamic Teaching and Learning, 2025)
Seeking knowledge is a fundamental obligation in Islam that encompasses intellectual, moral, and spiritual dimensions, positioning learning as both an educational process and an act of worship. This study aims to analyze the concept and practice of students’ pursuit of knowledge in Islam and to construct an Islamic educational framework for character formation. Using a qualitative approach with the living Quran and Hadith method, data were drawn from the Quran, Hadith, scholarly interpretations, expert opinions, and previous studies published in reputable international journals. Thematic analysis was conducted through Miles and Huberman’s interactive technique to identify recurring patterns and values. The findings reveal six essential concepts and practices for students in seeking knowledge: sincere intention for Allah, ethics toward teachers, diligence and perseverance, reliance on Allah, avoidance of sinful acts, and supplication. These elements highlight the integration of spirituality, ethics, and discipline in Islamic pedagogy. The study concludes that these six principles provide a practical framework for Islamic character education, offering guidance for educators and institutions to cultivate students with noble character and integrity in diverse educational contexts.